AKTUALISASI DIRI GENERASI Y DI INSTAGRAM - Bernadeta, Lenny Setyowati (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTNowadays, around us there are many teenagers who use social media as a means to actualize themselves, they are often referred to as Y Generation (Y Genes). Y Generation is the generation who was born in 1980 to 2000. The positive sides that they have a high self-confidence, strong in self-esteem, good in social networks, creative, multi-tasking, the generation who love the wireless world (Tulgan and Martin 2001, Beekman 2011). Through the technology, new media as a place for the generation of Y genes express themselves to gain recognition and self-existence they make use of social media, for example: their favorite is to take their picture by themselves (which famous as selfie in Indonesian) then upload them to social media, using social media such as instagram. The process of self-actualization by generation Y through social networking is done by displaying the profile photo, upload photos of their activities and write their status or feeling. The qualitative method was used in this research, self-presentation through dramaturgical theory. The techniques for collecting the data through: in-depth interviews with informants, observation, documentation and literature study. The researcher interviewed five person as the Y generation (3 female and 2 male), they were as students of Soegijapranata Catholic University in Semarang. Based on interviews the researcher concluded that the use of social media networking instagram for generation Y in actualize themselves was a positive activity, they displayed profile photos as attractive as possible, uploaded photos of individual activities as well as with the community, and wrote status as the fulfillment of the need for self-actualization and got a good impression on others. And this was appropriate with dramaturgy theory where people tend to show their positive side / front page toÂ  others.Key words: Gen Y, Social Media, Self Actualization